Stakeholder analysis of the Mato Grosso Northwest timber industry: A perspective on solid waste (Research, Society and Development, 2020)
The timber industry is prominent in the Mato Grosso state, however, it generates large amounts of waste. Knowing the sectors of the society involved in the industry and their interrelationships are fundamental for developing effective public policies. The objective of this paper is to survey key social groups about how to resolve wood waste generation in northwestern Mato Grosso state. We identified stakeholders who were then classified according to their degree of power and interest. Public policies were analyzed and discussed. Sixteen stakeholders were found, of which eight were considered in the high power and interest group. The public policies discussed are generic and comprehensive, which suggests implementation challenges. We concluded that high power/interest groups are fundamental for garnering support for policies, given their vested interest in the outcome. The following were suggested: greater availability and dissemination of information; greater synergy between existing institutions and policies; focusing on priority regions; and promoting incentive mechanisms.